EFEKTIVITAS EKSTRAK BUAH MENGKUDU (Morinda citrifolia) PADA PAKAN TERHADAP SINTASAN DAN PERTUMBUHAN BENIH IKAN PATIN (Pangasius hypophthalmus) - Wan Suha Salsabila; Andika Putriningtias; Suri Purnama Febri (Universitas Mataram, 2026)
As a freshwater commodity, catfish (Pangasius hypophthalmus) has a high market value, making it worthy of cultivation. The purpose of this study was to determine the optimal dosage of noni fruit extract for the survival and growth of catfish fry, which is then applied to commercial feed. In aquaculture, feed plays a crucial role in determining the success of fish growth. The catfish used were 8-10 cm in size. The method used in this study was a Completely Randomized Design (CRD) with four treatments and three replications. Where P1 (without giving noni extract), P2 (giving noni extract 5 ml/kg feed), P3 (giving noni extract 10 ml/kg feed) and P4 (giving noni extract 15 ml/kg feed. The results of the study showed that the best survival was in P3 (86.66%), the best absolute weight growth was in P3 (4.80g), the best absolute length growth was in P2 (1.04 cm), the best daily growth rate was in P3 (1.64%) and the best feed conversion ratio was in P3 (2.10%).